2002
DOI: 10.1107/s010827010200152x
|View full text |Cite
|
Sign up to set email alerts
|

A copper(II)–pyrazole complex cation with \bf \overline 3 imposed symmetry

Abstract: The reaction of Cu(ClO(4))(2) x 6H(2)O, NaAsF(6) and excess pyrazole yields hexakis(pyrazole-kappa N(2))copper(II) bis(hexafluoroarsenate), [Cu(C(3)H(4)N(2))(6)](AsF(6))(2) or [Cu(pzH)(6)](AsF(6))(2) (pzH is pyrazole), (I). The analogous hexakis(pyrazole-kappa N(2))copper(II) hexafluorophosphate perchlorate complex, [Cu(C(3)H(4)N(2))(6)](PF(6))(1.29)(ClO(4))(0.71) or [Cu(pzH)(6)](PF(6))(1.29)(ClO(4))(0.71), (II), is obtained in a similar fashion, using KPF(6) in place of NaAsF(6). Both compounds contain the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In our previous studies, we have demonstrated that the imidazole-containing curcumin analogue CRANAD-17 could specifically interrupt the copper induced crosslinking of Aβ, due to the imidazole moiety, which could interfere with the copper coordination with H13 and H14 of Aβ 17 . In CRANAD-28, the pyrazole ring could have the capability to coordinate with copper 38 , and thus may have the ability to compete with H13/H14 coordination. Therefore, it is reasonable to speculate that CRANAD-28 can also attenuate copper-induced crosslinking of Aβ.…”
mentioning
confidence: 99%
“…In our previous studies, we have demonstrated that the imidazole-containing curcumin analogue CRANAD-17 could specifically interrupt the copper induced crosslinking of Aβ, due to the imidazole moiety, which could interfere with the copper coordination with H13 and H14 of Aβ 17 . In CRANAD-28, the pyrazole ring could have the capability to coordinate with copper 38 , and thus may have the ability to compete with H13/H14 coordination. Therefore, it is reasonable to speculate that CRANAD-28 can also attenuate copper-induced crosslinking of Aβ.…”
mentioning
confidence: 99%
“…The electron donor (nitrogen) of non-substituted pyrazole unit can coordinate to many metal ions such as copper and vanadium, etc. (Otieno et al, 2002;Xing et al, 2007). When the carboxyl group as the substitutent at three or five position on the pyrazole ring is present, this will enhance the coordination capability of the pyrazole ring, and the substituted carboxyl group and the pyrazole ring with the metal ion can form a steady five-member cycle (Roussel et al, 2006).…”
Section: S1 Commentmentioning
confidence: 99%
“…For the coordination chemistry of similar pyrazole derivatives, see: Trofimenko (1972); Xing et al (2007); Infantes et al (1999). For related literature, see: Otieno et al (2002); Roussel et al (2006). (2) 153Symmetry codes: (i) Àx þ 1 2 ; y À 1 2 ; Àz þ 1 2 ; (ii) Àx; Ày þ 1; Àz.…”
Section: Related Literaturementioning
confidence: 99%
“…In recent years, we have investigated the coordination chemistry of metal complexes with Ncontaining heterocyclic derivatives (Maslejová et al, 2001;Boca et al, 2003;Svoboda et al, 2001). Pyrazole (pzH) forms a variety of metal complexes (Otieno et al, 2002;Steel, 1990;Trofimenko, 1972Trofimenko, , 1986. There has been one report of the crystal structure of a hydrate of [Ni(Oac) 2 (pzH) 4 ] (Doring et al, 1996).…”
Section: Commentmentioning
confidence: 99%
“…Bo˘ca et al, 2003;Svoboda et al, 2001). Pyrazole (pzH) forms a variety of metal complexes (Otieno et al, 2002;Steel, 1990;Trofimenko, 1972Trofimenko, , 1986. There has been only one report of the crystal structure of a hydrate of [Ni(ac) 2 (pzH) 4 ] (Doring et al, 1996).…”
Section: Crystal Datamentioning
confidence: 99%